Modelling of rigid walled enclosure couple to a flexible wall using matlab and ansys APDL - Izzuddin, Zaman; Syaiful Azmirul, Mohd Rozlan; Nor Azali, Azmir; Maznan, Ismon; M. A., Madlan; Musli Nizam, Yahya; Muhd Hafeez, Zainulabidin; M. S. M., Sani; M. F. M., Noh (IOP Publishing, 2017)
Generally, solutions to improve the noise problems in enclosure are to redesign or modifying the system such as increasing the thickness of the wall panels, enhancing the elasticity of the structure, and increase the damping mechanism of the wall structure. In this paper, the application of vibroacoustic modelling of enclosure coupled to a flexible wall was presented. The sound pressure characteristics of rigid walled enclosure, such as natural frequency and mode shape were determined using two approaches which are finite element simulation of Ansys® and mathematical model. The mathematical equations derived in Matlab® such as rigid walled enclosure and rigid walled enclosure coupled to flexible wall were used to validate finite element analysis (FEA). The result indicates that the theory and FEA display in a good agreement. Thus, proved that the FE model was accurate and can be applied in further research such as sound pressure and noise attenuation in enclosure.